The Effects Of Field Work Experience, The Role Of Specialized Job Fairs, And Motivation To Enter The Workforce On The Employment Readiness Of Students At SMKN 1 Surabaya - Mohamad Ilham Ardiansyah; Fitriana Rahmawati (Lembaga Riset dan Inovasi Almatani, 2026)
This study was motivated by the high rate of open unemployment among graduates of Vocational High Schools (SMK), indicating that students’ work readiness needs to be improved. Work readiness is influenced by various factors, including work experience and individual internal factors. This study aims to analyze the effect of Field Work Practice (PKL), the role of the Special Job Fair (BKK), and motivation to enter the workforce on the work readiness of students at SMKN 1 Surabaya. This study employed a quantitative approach with a descriptive method. The sample consisted of 103 twelfth-grade students from the Office Management and Business Services program at SMKN 1 Surabaya. The data analysis technique used multiple linear regression analysis with the help of SPSS 27.0. The results showed that Field Work Practice and motivation to enter the workforce have a positive and significant effect on students’ work readiness. Meanwhile, the role of the Special Job Fair does not have a significant partial effect on work readiness. However, simultaneously, all three variables have an effect on students’ work readiness